PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN HUTANG SEBAGAI VARIABEL INTERVENING - Irene Maitri Pandansari; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2016)
The aim of this study is to examine the influence of managerial ownership, institutional ownership and dividend policy on the firm value through debt policy as an intervening variable. The population used in this study consist of manufacture firms listed on the Indonesia Stock Exchange during the period 2010-2014. The sampling method used in this study is purposive sampling and obtained 90 samples. The analysis method used in this study is multiple linear regressions expanded with path analysis to examine the direct and indirect effect of managerial ownership, institutional ownership and dividend policy on firm value.There are three results of this study. First result of this study show that each variable of institutional ownership and dividend policy had positively and negatively significant influence on debt policy, while variable of managerial ownership had no significant influence on debt policy. Second, this study show that dividend policy had positively significant, and managerial ownership, institutional ownership and debt policy had negatively significant on firm value. Third result of this study show that debt policy can mediate the relationship of managerial ownership and dividend policy to firm value, while debt policy can’t mediate the relationship of institutional ownership to firm value.